Solar Photocatalytic Degradation of Sulfamethoxazole by TiO2 Modified with Noble Metals - Borowska, Ewa (2019)
Application of solar photocatalysis for water treatment is intensively studied. In this work, we investigated TiO2 modified with platinum (Pt/TiO2) and palladium (Pd/TiO2) using sulfamethoxazole (SMX) as the model contaminant. We considered the following parameters: (i) level of TiO2 modification with Pt/Pd, (ii) initial concentration of photocatalysts, (iii) geographic location where processes were conducted, and (iv) natural water matrix. The catalysts characterized by SEM, EDX, DRS, and XRD techniques showed successful deposition of Pd and Pt atoms on TiO2 surface that enabled light absorption in the visible (Vis) range, and therefore caused e cient SMX removal in all tested conditions. A comparison of the rate constants of SMX degradation in various conditions revealed that modification with Pd gave better results than modification with Pt, which was explained by the better optical properties of Pd/TiO2. The removal of SMX was higher with Pd/TiO2 than with Pt/TiO2, independent of the modification level. In the experiments with the same modification level, similar rate constants were achieved when four times the lower concentration of Pd/TiO2 was used as compared with Pt/TiO2. Formation of four SMX transformation products was confirmed, in which both amine groups are involved in photocatalytic oxidation. No toxic e ect of post-reaction solutions towards Lepidium sativum was observed.